HUBUNGAN ANTARA PERILAKU BULLYING DENGAN KESEHATAN MENTAL SISWA KELAS VIII DI SMP NEGERI 2 KENDAL - Belvaza Feilasifa; Anwar Sutoyo (Jurnal Edukasi : Jurnal Bimbingan Konseling, 2022)
This study aims to determine whether or not there is a relationship between bullying behavior and the mental health of class VIII students at SMP Negeri 2 Kendal. This type of research is descriptive correlational quantitative research. The subjects of this study were 256 students of class VIII and as a sample 64 students who had high, medium, and low levels of bullying behavior and mental health. The sampling technique was taken using a proportionate stratified random sampling technique. The data collection method used a bullying behavior scale and a mental health scale. The data analysis technique used was a descriptive analysis of the percentage of product-moment correlation analysis, and hypothesis testing using the SPSS version 22 application tool. The results showed that the majority of studentsâ€™ levels of bullying behavior and mental health were dominated in the moderate category, with bullying behavior at 64.1% and mental health at 67.2%. In addition, the hypothesis test for the normality test obtained a significant result of 0.200 meaning that the normal distribution and linearity test had a significant result of 0.818 linear means. Furthermore, the data obtained from the product-moment correlation analysis results obtained a Pearson correlation of -0.584 and a Sig value. (2-tailed) with a value of 0.000 < 0.05 then the research hypothesis is accepted. Based on the results of the study, it can be concluded that there is a significant negative relationship between bullying behavior and the mental health of class VIII students at SMP Negeri 2 Kendal.Â Â